(untitled) (Journal of Naval Architecture and Marine Engineering, 2026)
The objective of our work is to create a numerical model for predicting the thermal profile in weld joints of modified 9Cr-1Mo steel plates by considering the effects of welding heat input. This paper mainly focused on the thermal analysis of the Submerged Arc Welding process (SAW) using a moving heat source model (Gaussian distribution) of Modified 9Cr-1Mo steel. The study develops a general methodology of the finite difference method (FDM) using MATLAB code to accurately estimate the thermal profile. The results indicate a good agreement between the numerical and experimental results, with an overall error percentage estimated to be between 6-9%, confirming the capability and reliability of the proposed numerical model. Finally, the study demonstrates the essential role of various parameters in affecting the thermal profile. Journal of Naval Architecture and Marine Engineering, 23(1), 2026, PP. 61-74